Implementation of Global Sustainable Development Goals at the Local Level: Studies of Home Industry in Kedunglengkong Village, Simo sub-district, Boyolali District, Central Java Province, Indonesia - Puji Hardati; Dewi Liesnoor Setyowati; Satya Budi Nugraha; M Fikri Amrullah; Amanah Kartika Ratnaningsih (Indonesian Journal of Conservation, 2024)
A Development is carried out to reduce disparities between regions. The increase in human population is followed by the intensity of land and resource use, interactions and changes that occur, until nature has boundaries, or planetary boundaries. Sustainable development has 17 goals that are universal, comprehensive and involve all countries. How to implement sustainable development goals at the local level. This research aims to analyze the implementation of sustainable development goals at the local level, namely responsible industry and consumption. This research uses a quantitative approach, the research location is Kedunglengkong Village, Simo District, Boyolali Regency, Central Java Province. The research population is home industry owners with a population of 35 people, using total sampling or the entire population as the unit of analysis. The research variables are indicators of sustainable development goal 12, responsible consumption and productive patterns. The data source used is primary data collected through observation and in-depth interviews. Data analysis uses descriptive percentages, with tables and figures. The research results show that there are 35 home industries that use raw materials from plastic waste. The raw material used is plastic waste originating from the surrounding environment. Home industries that use plastic waste as raw material are a concrete manifestation of the implementation of responsible industry and consumption, in accordance with the Sustainable Development Goal indicators at point 12.5., namely by 2030, substantially reducing waste production through prevention, reduction, recycling and use return. Furthermore, in indicator 12.5.1 (a) the amount of recycled waste generated.